Development and commissioning of controlled struvite crystallization in pilot scale - Ali, Md. Imtiaj; Schneider, Philip A. (2006)
This paper focuses on the design of a nutrient recovery scheme, conducted in a fed-batch controlled crystallization technique, leading to the formation of struvite (Magnesium Ammonium Phosphate). The controlled crystallization technique included the control of solution pH and concentration during each experiment. Characterization of struvite crystal growth was conducted by CSD (crystal size distribution) analysis of growing struvite. Controlled crystallization showed significant growth of struvite crystals by surface diffusion, whereas faulty control initiated significant amount of fines.